Local delivery of doxorubicin nanocrystals from electrospun nanofibers - Ventura, Tatiana (2017)
The objective of this study is to develop a novel system for local application of DOX either in surgical loci or in a topical application device enabling a controlled release of the drug. The developed system involves the encapsulation of DOX into electrospun polymeric nanofibers. Chosen polymers were polyoxyethilene (PEO) and polycaprolactone (PCL).